Green energy generation from plant microbial fuel cells (PMFC) using compost and a novel clay separator. (June 2017) - Sophia, A. Carmalin; Sreeja, S.
Abstract: This research study investigates the influence of three different plants ( Brassica juncea, Trigonella foenum-graecum and Canna Stuttgart ) and compost addition, on bioenergy generation in a PMFC. The studies revealed that Trigonella foenum-graecum and Canna stuttgart exhibit higher bio-energy generation compared to Brassica juncea . Trigonella foenum-graecum being a leguminous plant and Canna Stuttgart, tuberous plant may harbor high densities exudates and hence microorganisms. The high power density may be attributed to plant type and addition of compost to the soil- hence resulting root deposits. Further in depth research is necessary to explore the reason behind higher concentrations of exudates. Canna stuttgart (tuberous plant) showed the highest power output (power density of 222 mW m −2 conversion efficiency of 0.022%) with least diurnal fluctuations. A novel clay mix separator in the place of membranes was used for the very first time in the present study. The use of laboratory materials such as artificial growth medium, ferricyanide and commercial membranes has been avoided thus simplifying the system design and cost. Development of the PMFC technology may lead to a new generation of sustainable, environment integrated energy harvesting systems.